CircSLC7A6 promotes the progression of Wilms’ tumor via microRNA-107/ ABL proto-oncogene 2 axis - Jiaju Xu (Taylor & Francis Group, 2021)
The dysregulation of circular RNAs (circRNAs) has been proved to be involved in the carcinogenesis of various cancers. Nevertheless, the biological function of circSLC7A6 remains unclear in Wilms’ tumor (WT). In our study, we found that circSLC7A6 was upregulated in cancerous WT tissues and cells. Cell apoptosis was increased while cell viability, migration, and invasion were repressed by circSLC7A6 silencing. Besides, circSLC7A6 knockdown suppressed WT tumor growth in vivo. miR-107 was identified as a direct target of circSLC7A6, and circSLC7A6 could negatively regulate miR-107 expression. In addition, circSLC7A6 knockdown inhibited WT progression, while the effect was partially abolished by the downregulation of miR-107. Additionally, ABL proto-oncogene 2 axis (ABL2) was verified as a downstream gene of miR-107, and circSLC7A6 could upregulate ABL2 expression by serving as a ceRNA of miR-107. Moreover, functional assays revealed that ABL2 overexpression reversed the impact of circSLC7A6 depletion on cell proliferation, migration, invasion, and apoptosis of WT. In conclusion, the present study demonstrated that circSLC7A6 facilitated WT progression by upregulating ABL2 through inhibiting miR-107 expression. These results suggested that circSLC7A6 might serve as a potential therapeutic target for WT.